2001
DOI: 10.1046/j.1365-201x.2001.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and oxidative signalling in skeletal muscle

Abstract: A growing body of literature indicates that cytokines regulate skeletal muscle function, including gene expression and adaptive responses. Tumour necrosis factor-alpha (TNF-alpha) is the cytokine most prominently linked to muscle pathophysiology and, therefore, has been studied most extensively in muscle-based systems. TNF-alpha is associated with muscle catabolism and loss of muscle function in human diseases that range from cancer to heart failure, from arthritis to AIDS. Recent advances have established tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(115 citation statements)
references
References 85 publications
1
111
2
1
Order By: Relevance
“…Reactive oxygen species (ROS) is implicated in muscle wasting, and LPS is known to induce oxidative stress [Reid and Li, 2001]. However, our finding that activation of the redoxsensitive transcription factor NF-κB [Li et al, 1999] by LPS in muscle is not affected by curcumin suggests that curcumin does not inhibit atrogin-1/MAFbx upregulation by functioning as a general antioxidant.…”
Section: Discussioncontrasting
confidence: 52%
“…Reactive oxygen species (ROS) is implicated in muscle wasting, and LPS is known to induce oxidative stress [Reid and Li, 2001]. However, our finding that activation of the redoxsensitive transcription factor NF-κB [Li et al, 1999] by LPS in muscle is not affected by curcumin suggests that curcumin does not inhibit atrogin-1/MAFbx upregulation by functioning as a general antioxidant.…”
Section: Discussioncontrasting
confidence: 52%
“…Muscle strenuous contraction induces protein loss and cachexia (25). However, we found no evidence to support respiratory muscle overloading (as discussed above), which could lead to increased expression of muscle cytokines.…”
Section: The Experimental Modelcontrasting
confidence: 50%
“…Since TNFα can also stimulate the production of mitochondrial ROS, 62 this could create a positive feedback loop whereby the increased ROS cause further activation of NF-κBa s well as having their own deleterious effects on the muscle. 38 This idea is supported by a recent paper which reported that mdx mice injected with an anti-TNFα antibody,R emicade, displayed less muscle necrosis and reduced inflammatory cell infiltration than control mdx mice.…”
Section: Rosand Inflammatory Damage Ofdystrophic Musclementioning
confidence: 99%